2002
DOI: 10.1111/1475-6803.00022
|View full text |Cite
|
Sign up to set email alerts
|

Stock Returns and Operating Performance of Securities Issuers

Abstract: We examine long-run stock returns and operating performance around firms' offerings of common stock, convertible debt, and straight debt from 1985 to 1990. We find that pre-issue abnormal returns are positive and significant for stock issuers, but not for convertible and straight debt issuers. The post-issue mean returns show that common stock and convertible debt issuers experience underperformance during the post-issue periods, but straight debt issuers do not. Consistent with these results, common stock iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
18
3
Order By: Relevance
“…A number of studies provide evidence of abnormal stock performance following issues of convertible debt (e.g., Lee and Loughran, 1998;McLaughlin et al, 1998;Spiess and Affleck-Graves, 1999;Eckbo et al, 2000;Bae et al, 2002). In addition, McLaughlin et al and Bae et al document post-issue declines in operating performance subsequent to convertible debt issues.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies provide evidence of abnormal stock performance following issues of convertible debt (e.g., Lee and Loughran, 1998;McLaughlin et al, 1998;Spiess and Affleck-Graves, 1999;Eckbo et al, 2000;Bae et al, 2002). In addition, McLaughlin et al and Bae et al document post-issue declines in operating performance subsequent to convertible debt issues.…”
Section: Introductionmentioning
confidence: 99%
“…Even though stock returns are not observable for the majority of firms in our sample, note that Bae et al (2002) show that operating performance and stock performance behave qualitatively similar for these types of analyses. 4 For example, L贸pez-Gracia and Sogorb-Mira (2008) found that (Spanish) SMEs behave like predicted by the pecking order theory, which is based on the work by Myers and Majluf (1984).…”
Section: Propensity Score Matchingmentioning
confidence: 78%
“…In Hansen and Crutchley (1990), the authors reported a financing year downturn in earnings, concluding that firms issue debt to survive bad years. McLaughlin et al (1998) as well as Bae et al (2002) showed that all types (e.g. equity, convertibles, debt, etc.)…”
Section: Related Literaturementioning
confidence: 98%
“…Companies therefore appear to time their financings to take advantage of favourable market conditions. Also, a number of studies have found that earnings performance declines after a financing announcement (Hansen and Crutchley, 1990;Patel et al, 1993;Loughran and Ritter, 1997;McLaughlin et al, 1996McLaughlin et al, , 1998aBae et al, 2002). This again would appear supportive of timing playing a role in the financing announcement.…”
Section: Article In Pressmentioning
confidence: 88%
“…The principal results are that companies do indeed follow a pecking order (Kester, 1986;Burton et al, 1993;ShyamSunder and Myers, 1995;Slovin et al, 2000); with the share price declining upon announcement of a share issue (Asquith and Mullins, 1986;Hudson et al, 1993;Spiess and Affleck-Graves, 1995;Bae et al, 2002). 6 Contradictory evidence has been generated with respect to debt issues: with one group of papers finding no effect, as expected under pecking order theory (Dann and Mikkelson, 1984;Eckbo, 1986;Mikkelson and Partch, 1986); and others finding a positive announcement effect to debt issues (Kim and Stulz, 1988;Ikenberry et al, 1995;Bae et al, 2002). Supporting evidence for the hypothesis that companies tend to issue when asymmetries are minimised has been found by a number of studies (Korajczyk et al, 1991;Dierkins, 1991;Manuel et al, 1993).…”
Section: Article In Pressmentioning
confidence: 99%